Numerical Simulation Analysis of NPR Anchorage Monitoring of Bedding Rock Landslide in Open-Pit Mine. (6th January 2020) - Zhang, Kai; Yang, Xiaojie; Cui, Xuebin; Wang, Yong; Tao, Zhigang
Abstract : Nanfen open-pit iron mine is the largest single open-pit mine in Asia. Because of the lag of the extension project, the section has slowly spread in the shape of "V, " and disasters such as landslides occur frequently. In this study, first, the NPR anchor cable monitoring, which shows supernormal mechanical characteristics and can realize the monitoring and early warning target for the whole landslide process and early warning curve of bedding rock "2016-1101 landslide" in the lower wall of Nanfen open-pit mine, was analyzed, revealing the failure process of the bedding rock landslide and the force evolution characteristics of the NPR anchor cable. Then, based on the Fish language in FLAC3D and 3DEC software, the mechanical model of the NPR anchor cable was constructed, and numerical simulation was performed on the whole process of "16-1101 landslide" induced by accumulation of old landslide body. The results of this study indicate that the stress monitoring curves and failure characteristics of the NPR anchor cables in the whole process of landslide by the two numerical simulation methods are basically consistent with the field measurement results, providing a theoretical and practical basis for the mechanistic analysis and numerical simulation of other similar slopes.